TRPV4 Blockade Preserves the Blood–Brain Barrier by Inhibiting Stress Fiber Formation in a Rat Model of Intracerebral Hemorrhage - Zhao, Hengli; Zhang, Kaiyuan; Tang, Rongrui; Meng, Hui; Zou, Yongjie; Wu, Pengfei; Hu, Rong; Liu, Xin; Feng, Hua; Chen, Yujie (Frontiers in Molecular Neuroscience, 2018)
Blood-brain barrier (BBB) disruption and subsequent brain edema play important roles in the secondary neuronal death and neurological dysfunction that are observed following intracerebral hemorrhage (ICH). In previous studies, transient receptor potential vanilloid 4 (TRPV4), a calcium-permeable mechanosensitive channel, was shown to induce cytotoxicity in many types of cells and to play a role in orchestrating barrier functions. In the present study, we explored the role of TRPV4 in ICH-induced brain injury, specifically investigating its effect on BBB disruption. Autologous arterial blood was injected into the basal ganglia of rats to mimic ICH. Adult male Sprague Dawley rats were randomly assigned to sham and experimental groups for studies on the time course of TRPV4 expression after ICH. The selective TRPV4 antagonist HC-067047 and TRPV4 siRNA were administered to evaluate the effects of TRPV4 inhibition. GSK1016790A, a TRPV4 agonist, was administered to naive rats to verify the involvement of TRPV4-induced BBB disruption. A PKC inhibitor, dihydrochloride (H7), and a selective RhoA inhibitor, C3 transferase, were administered to clarify the involvement of the PKCα/RhoA/MLC2 pathway following ICH. Post-ICH assessments including functional tests, brain edema measurements, Evans blue extravasation, western blotting and immunohistochemical assays were performed. TRPV4 inhibition remarkably ameliorated neurological symptoms, brain edema, and neuronal death, as well as BBB disruption, 24–72 hours following ICH. Meanwhile, TRPV4 blockade preserved the expression of adherens and tight junction proteins, as well as BBB integrity, by inhibiting stress fiber formation, which might be correlated with the regulation of components of the PKCα/RhoA/MLC2 pathway. Furthermore, adherens and tight junction protein degradation induced by GSK1016790A treatment in naive rats was also related to PKCα/RhoA/MLC2-pathway-mediated stress fiber formation. Based on these findings, therapeutic interventions targeting TRPV4 may represent a novel approach to ameliorate secondary brain injury following ICH.